The Relation Between Tinnitus and a Neurovascular Conflict of the Cochleovestibular Nerve on Magnetic Resonance Imaging. Issue 1 (January 2020) - Peters, Thomas T. A.; van den Berge, Minke J. C.; Free, Rolien H.; van der Vliet, Anton M.; Knoppel, Hanna; van Dijk, Pim; Hofman, Rutger
Abstract : Introduction: Magnetic resonance (MR) imaging is often used in diagnostic evaluation of tinnitus patients. Incidental findings like a neurovascular conflict (NVC) in the cerebellopontine angle are often found; however, the diagnostic value of this finding remains unclear. The aim of this study is to investigate whether the type or degree of compression of the vestibulocochlear nerve is of diagnostic value in patients with a NVC. Methods: A retrospective study was performed in 111 tinnitus patients with available MR imaging between 2013 and 2015. Clinical and audiometric variables were gathered and MR imaging was reevaluated by two neuroradiologists. NVCs were analyzed using a grading system based on previous research by Sirikci et al. Results: In total, 220 ears were available for assessment. In patients with unilateral tinnitus a loop compression and an indentation of the cochleovestibular nerve were more frequent than in patients with bilateral tinnitus. However, there was no significant difference in distribution of the type of compression between tinnitus and nontinnitus ears. Patient with unilateral tinnitus had a significantly higher degree of hearing loss in the symptomatic ear, compared with the asymptomatic ear and with the bilateral tinnitus group. Also, it was found that the degree of hearing loss did not differ between the various types of compression. Conclusion: This study did not find a diagnostic value of specific types of compression in patients with a NVC. Although the distribution of NVC classification was different in patients with unilateral and bilateral tinnitus, there was no definite relation between the type of NVC and the presence of ipsilateral tinnitus. Also, the degree of hearing loss was not related to specific types of NVC.